2011
DOI: 10.1111/j.1365-2699.2011.02586.x
|View full text |Cite
|
Sign up to set email alerts
|

The extraordinary journey of Peperomia subgenus Tildenia (Piperaceae): insights into diversification and colonization patterns from its cradle in Peru to the Trans-Mexican Volcanic Belt

Abstract: Aim : Peperomia subgenus Tildenia consists of c. 60 species growing in seasonal habitats of Neotropical mountain areas from Mexico to Argentina. The subgenus can be split geographically, with almost equal diversity in the Northern Hemisphere (centred in Mexico and Guatemala) and in the Southern Hemisphere (centred in Peru and Bolivia). Only a few species are known from a limited number of localities between these two hotspots. As such, Tildenia is an ideal candidate with which to test time, direction and mode … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 100 publications
(205 reference statements)
0
24
0
1
Order By: Relevance
“…The Amotape-Huancabamba zone might represent a dispersal barrier for high-elevation lineages under current climatic conditions. Support for this idea has been found in the distribution of groups such as Lithospermum (Boraginaceae; Weigend et al, 2010), Macrocarpea (Gentianaceae; Struwe et al, 2009), Nasa (Loasaceae; Weigend, 2002), Peperomia (Piperaceae; Symmank et al, 2011). The Central Andes are situated between the Amotape-Huancabamba zone and the southern limit of the dry Puna around 25-29 • S, where the precipitation regime changes from summer-rainfall to winter-rainfall (Luebert and Pliscoff, 2006), which is paralleled by floristic turnover (Villagrán et al, 1983;Martínez-Carretero, 1995;Arroyo et al, 1997Arroyo et al, , 1998.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…The Amotape-Huancabamba zone might represent a dispersal barrier for high-elevation lineages under current climatic conditions. Support for this idea has been found in the distribution of groups such as Lithospermum (Boraginaceae; Weigend et al, 2010), Macrocarpea (Gentianaceae; Struwe et al, 2009), Nasa (Loasaceae; Weigend, 2002), Peperomia (Piperaceae; Symmank et al, 2011). The Central Andes are situated between the Amotape-Huancabamba zone and the southern limit of the dry Puna around 25-29 • S, where the precipitation regime changes from summer-rainfall to winter-rainfall (Luebert and Pliscoff, 2006), which is paralleled by floristic turnover (Villagrán et al, 1983;Martínez-Carretero, 1995;Arroyo et al, 1997Arroyo et al, , 1998.…”
Section: Introductionmentioning
confidence: 93%
“…In Peperomia subg. Tildenia, Central American taxa originated from central Andean ancestors around 15 Ma (Symmank et al, 2011). These authors suggest a northern Andean track and subsequent extinction of the group in the Northern Andes, since the current northern limit of Peperomia subg.…”
Section: Biogeographical Relationships Of the Andean Floramentioning
confidence: 99%
See 1 more Smart Citation
“…The high number of species shared between the Bolivian Andes and the central Andean region was already commented on by Linares-Palomino et al (2011), who found a strong floristic similarity between these two regions. Vicariance and long-distance dispersal events in combination have been discussed as the basis of widespread distributions of Neotropical SDTF species (Prado & Gibbs, 1993;Pennington et al, 2006;Symmank et al, 2011;Pennington & Lavin, 2016).…”
Section: Neotropicsmentioning
confidence: 99%
“…The existence of island arcs between the two continents at around 15 mya (Krzywinski et al, ) could have facilitated this LDD. Indeed, biotic exchange for numerous plant lineages has been invoked before complete closure (e.g., Chloranthaceae, Antonelli & Sanmartin, ; Valerianaceae, Bell & Donoghue, ; Ephedra , Ickert‐Bond et al, ; Begonia , Moonlight et al, ; Piperaceae, Symmank et al, ). Colonization of Chile via LDD from the northern Andes led to the diversification of Chilean Selkirkia s.l.…”
Section: Discussionmentioning
confidence: 99%